SUPPORTING INDIGENOUS SOCIAL WORKERS IN FRONT-LINE PRACTICE - Burke, Susan (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2018)
Indigenous peoples have been reclaiming jurisdiction over their child welfare services and Western society has been increasingly acknowledging that Indigenous peoples are in the best position to provide these services. While the number of Indigenous social workers has historically been low, especially when compared to the population they serve, their numbers seem to be on the rise. In spite of that reality, most social service organizations continue to operate from a Western perspective, with little attention paid to the ways in which they must change in order to provide space for the Indigenous social workers they employ. This study explores the experiences of nine First Nations and Métis social workers in British Columbia (BC). The researcher, a Métis scholar and former child welfare social worker, conducted data collection and analysis through a Métissage framework, using semi-structured interviews. Thematic analysis revealed nine themes, including the need for (1) Knowledgeable leadership that supports autonomy; (2) Flexibility in practice; (3) Policy that fits both Indigenous and Western paradigms; (4) Relationships with other supportive social workers; (5) Support to navigate overlap between the personal and the professional; (6) Set standards/experienced co-workers; (7) Equitable workplace resources; (8) Respect regarding Indigenous identity, and; (9) Supports to maintain wellness. Recommendations suggest how this information can be used by organizations to better support the Indigenous social workers they employ.